Influence of different wavelengths peaks in LED units on the degree of conversion of orthodontic composites - Amato, Patricia; Martins, Lidia P. [UNESP]; Gatti, Alexandre; Pretel, Hermes [UNESP]; Martins, Renato P. [UNESP] (Elsevier B.V., 2016)
Objective: The aim of this study was to assess the influence of adding a second wavelength peak (400 nm) to a light-emitting diode (LED) unit on the degree of conversion (DC) of two commercial orthodontic composites, as well as comparing the DC of those two composites. Methods: Transbond XT and Opal Bond MV were the composites used for the tests, cured either with second-or third-generation LED units adjusted to produce the same power density on a given time. Analysis of DC was performed by using the Fourier-transformed infrared spectroscopy in four groups of 5 specimens each divided according to the composites and LED curing units being used. The results, which were normally distributed, were analyzed using a two-way ANOVA test. Results: The composites showed very similar degrees of conversion when light-cured with second-generation (74.3%) and third-generation (73.2%) LED light-curing units. The Opal Bond MV composite had a higher degree of conversion (81.9%) than the Transbond XT composite (65.7%). No interaction was found (P = 0.56) between the composites and the LED curing units, regardless of their wavelength, on the degree of conversion. Conclusion: There was no influence of either a second- or third-generation LED curing unit on orthodontic composites. (C) 2016 World Federation of Orthodontists.
Keywords: Composite resins; FTIR; Orthodontics; Dual-peak